Vibration mitigation of long-span bridges with damped outriggers. (15th November 2022) - Chen, Lin; Liu, Zhanhang; Nagarajaiah, Satish; Sun, Limin; Zhao, Lin; Cui, Wei
Abstract: Long-span bridges have low vibration frequencies and small intrinsic damping, and hence are subjected to large-amplitude vibrations, e.g., vortex-induced vibrations (VIVs), which jeopardize the serviceability and safety of the bridge structures. This study proposes a novel concept to supplement damping to such bridges for multimode vibration mitigation, by damping rotations of the bridge girder during vertical and torsional vibrations instead of translational displacements that have been previously the focus of relevant studies. A salient advantage of the concept is that bridge girder rotations near its ends are relatively large during vibrations enabling adequate supplemental damping and also convenient implementation. The concept is realized by a damped outrigger, consisting of a stiff outrigger rigidly connected to the bridge girder and horizontal dampers connecting the end of the outrigger to a bridge tower or a pier. A tensioned beam with rotational constraints is first used to demonstrate damping effects of damped outriggers on suspension bridges. Considering practical parameter ranges, the maximal damping ratio provided by one damped outrigger to a specific mode is about 1.0%. Influences of the relative importance of axial tension and bending stiffness and outrigger stiffness are studied. Furthermore, finite element analyses of an existing suspension bridge with damped outriggers are conducted to verify the damping performance. Numerical results show that by installing one damped outrigger, 6 out of 7 modes that have been involved in VIV events of the bridge can achieve a damping ratio of approximately 1.0% or above. By installing damped outriggers at the two towers, more modes can achieve a relatively large damping ratio, suggesting excellent performance of damped outriggers in suppressing multimode vibrations of long-span bridges. Highlights: Damped outriggers proposed for vibration mitigation of long-span bridges for the first time. Damping effect studied via a simplified model of a suspension bridge with damped outriggers. Excellent performance in multimode vibration mitigation verified via finite element analyses. Demonstration via a case study of an existing long-span suspension bridge.